Resistance to bio-insecticides or how to enhance their sustainability: a review - Siegwart, Myriam; Graillot, Benoit; Blachere Lopez, Christine; Besse, Samantha; Bardin, Marc; Nicot, Philippe C.; Lopez-Ferber, Miguel (Frontiers in Plant Science, 2015)
After more than 70 years of chemical pesticide use, modern agriculture is increasingly using biological control products. Resistances to conventional insecticides are wide spread, while those to bio-insecticides have raised less attention, and resistance management is frequently neglected. However, a good knowledge of the limitations of a new technique often provides greater sustainability. In this review, we compile cases of resistance to widely used bio-insecticides and describe the associated resistance mechanisms. This overview shows that all widely used bio-insecticides ultimately select resistant individuals. For example, at least 27 species of insects have been described as resistant to Bacillus thuringiensis toxins. The resistance mechanisms are at least as diverse as those that are involved in resistance to chemical insecticides, some of them being common to bio-insecticides and chemical insecticides. This analysis highlights the specific properties of bio-insecticides that the scientific community should use to provide a better sustainability of these products.